Human rights in education, science, and culture : legal developments and challenges - Donders, Yvonne; Volodin, Vladimir (Routledge ; UNESCO Publishing, 2016)
Human rights are at the heart of UNESCO's work in the fields of education, science and culture. Conceived from an international human rights legal framework, this publication combines insights into the content, scope of application and corresponding state obligations of these rights with analyses of issues relating to their implementation.--Publisher's description.